Analysis of POAC managerial functions in the management of zakat mal at LAZISMU in Langsa city - Barezi Putra Sentosa; Mastura; Muhammad Uzair Zulkifly; Syamsul Rizal; Abdul Hamid (ASNAF : Journal of economic welfare, philantrophy, zakat and waqf, 2026)
Abstract (English version) Objective – Zakat institutions have a strategic role in distributing funds to alleviate poverty, but the management of zakat, infaq, and shadaqah funds at LAZISMU also requires good and structured management to ensure that the social activities carried out can have a real impact on people in need. The purpose of this study is to analyze the implementation of the POAC management function (Planning, Organization, Mobilization, and Control) in the management of zakat by LAZISMU Langsa City and how the strategy supports the effectiveness of distributing zakat funds to mustahiq. Methodology – This study uses a qualitative research method with a descriptive approach. The object of this research is Head, Secretary  and muzakki of LAZISMU Langsa City. Data collection techniques through interviews, observations, and documentation. Data analysis is carried out by reducing data, presenting data, and drawing conclusions based on a descriptive analytical approach. Research Results – The results of the study show that LAZISMU Langsa City has implemented the four management functions in a structured manner. Planning is carried out through the preparation of RAPBL based on six main programs, accompanied by a strategy to socialize zakat to the community. The organization of the institution is structured from the central to regional levels with a clear division of tasks. The distribution of zakat is carried out through consumptive and productive approaches. Supervision is carried out through a periodic reporting system and the involvement of community leaders to ensure transparency and accountability. LAZISMU Langsa City has a fairly clear and directed management plan so that it makes it easier to achieve the targets and goals that have been set. These results show that the implementation of POAC has been carried out, but improvements are still needed in terms of human resources and increased public understanding of the Langsa City LAZISMU Zakat Institution. Limitations – This study has limitations in terms of its scope, which is focused only on the city of Langsa, and does not describe the community's overall perception of the program's effectiveness. Further research could expand the scope of the study and involve more respondents to obtain a more comprehensive picture. Practical Implications – The implications of this study provide a practical contribution to the management of zakat institutions, especially in strengthening POAC management-based governance. The implementation of systematic planning through the RAPBL is able to increase the effectiveness of the program and ensure alignment between the objectives of the Institution and the needs of mustahiq. For the long term, it is better for zakat institutions to optimize productive zakat programs that are oriented towards economic empowerment. Originality/value - This study emphasizes the relationship between managerial functions and the effectiveness of zakat distribution, especially in increasing transparency, accountability, and program impact.   Abstrak (versi bahasa) Tujuan – Lembaga zakat memiliki peran strategis dalam mendistribusikan dana untuk mengurangi kemiskinan, namun pengelolaan dana zakat, infaq, dan syaqah di LAZISMU juga membutuhkan pengelolaan yang baik dan terstruktur untuk memastikan bahwa kegiatan sosial yang dilakukan dapat memberikan dampak nyata pada masyarakat yang membutuhkan. Tujuan penelitian ini adalah untuk menganalisis implementasi fungsi pengelolaan POAC (Perencanaan, Pengorganisasian, Mobilisasi, dan Pengendalian) dalam pengelolaan zakat oleh LAZISMU Kota Langsa dan bagaimana strategi tersebut mendukung efektivitas pendistribusian dana zakat kepada mustahiq. Metodologi – Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan deskriptif. Objek penelitian ini adalah Kepala, Sekretaris, dan muzakki LAZISMU Kota Langsa. Teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Analisis data dilakukan dengan mereduksi data, menyajikan data, dan menarik kesimpulan berdasarkan pendekatan analitis deskriptif. Hasil Penelitian – Hasil penelitian menunjukkan bahwa LAZISMU Kota Langsa telah mengimplementasikan keempat fungsi pengelolaan tersebut secara terstruktur. Perencanaan dilakukan melalui penyusunan RAPBL berdasarkan enam program utama, disertai dengan strategi sosialisasi zakat kepada masyarakat. Organisasi lembaga ini terstruktur dari tingkat pusat hingga regional dengan pembagian tugas yang jelas. Distribusi zakat dilakukan melalui pendekatan konsumtif dan produktif. Pengawasan dilakukan melalui sistem pelaporan berkala dan keterlibatan tokoh masyarakat untuk memastikan transparansi dan akuntabilitas. LAZISMU Kota Langsa memiliki rencana pengelolaan yang cukup jelas dan terarah sehingga memudahkan pencapaian target dan tujuan yang telah ditetapkan. Hasil ini menunjukkan bahwa implementasi POAC telah dilakukan, tetapi masih diperlukan perbaikan dalam hal sumber daya manusia dan peningkatan pemahaman masyarakat terhadap Lembaga Zakat LAZISMU Kota Langsa. Keterbatasan – Studi ini memiliki keterbatasan dalam hal cakupannya, yang hanya berfokus pada kota Langsa, dan tidak menggambarkan persepsi masyarakat secara keseluruhan tentang efektivitas program. Penelitian lebih lanjut dapat memperluas cakupan studi dan melibatkan lebih banyak responden untuk mendapatkan gambaran yang lebih komprehensif. Implikasi Praktis – Implikasi dari studi ini memberikan kontribusi praktis terhadap pengelolaan lembaga zakat, khususnya dalam memperkuat tata kelola berbasis manajemen POAC. Implementasi perencanaan sistematis melalui RAPBL mampu meningkatkan efektivitas program dan memastikan keselarasan antara tujuan Lembaga dan kebutuhan mustahiq. Untuk jangka panjang, lebih baik bagi lembaga zakat untuk mengoptimalkan program zakat produktif yang berorientasi pada pemberdayaan ekonomi. Orisinalitas/nilai - Studi ini menekankan hubungan antara fungsi manajerial dan efektivitas distribusi zakat, khususnya dalam meningkatkan transparansi, akuntabilitas, dan dampak program.